Social determinants of health and retention in HIV care in a clinical cohort in Ontario, Canada. Issue 7 (3rd July 2017) - Rachlis, Beth; Burchell, Ann N.; Gardner, Sandra; Light, Lucia; Raboud, Janet; Antoniou, Tony; Bacon, Jean; Benoit, Anita; Cooper, Curtis; Kendall, Claire; Loutfy, Mona; Wobeser, Wendy; et al.
ABSTRACT: Continuous HIV care supports antiretroviral therapy initiation and adherence, and prolongs survival. We investigated the association of social determinants of health (SDH) and subsequent retention in HIV care in a clinical cohort in Ontario, Canada. The Ontario HIV Treatment Network Cohort Study is a multi-site cohort of patients at 10 HIV clinics. Data were collected from medical charts, interviews, and via record linkage with the provincial public health laboratory for viral load tests. For participants interviewed in 2009, we used three-category multinomial logistic regression to identify predictors of retention in 2010–2012, defined as (1) continuous care (≥2 viral loads ≥90 days in all years; reference category); (2) discontinuous care (only 1 viral load/year in ≥1 year); and (3) a gap in care (≥1 year in 2010–2012 with no viral load). In total, 1838 participants were included. In 2010–2012, 71.7% had continuous care, 20.9% had discontinuous care, and 7.5% had a gap in care. Discontinuous care in 2009 was predictive ( p < .0001) of future retention. SDH associated with discontinuous care were Indigenous ethnicity, being born in Canada, being employed, reporting hazardous drinking, and non-injection drug use. Being a heterosexual male was associated with having a gap in care, and being single and younger were associated with discontinuous care and a gap in care. Various SDH were associated with retention. Care discontinuity was highly predictive of future gaps. Targeted strategic interventions that better engage those at risk of suboptimal retention merit exploration. Abbreviations: AOR: adjusted odds ratio; ART: antiretroviral therapy; AUDIT: Alcohol Use Disorders Identification Test; CES-D: Center for Epidemiologic Studies Depression Scale; CIs: confidence intervals; HIV: human immunodeficiency virus; IQR: interquartile range; MSM: men who have sex with men; NA-ACCORD: North American AIDS Cohort Collaboration on Research and Design; OCS: Ontario HIV Treatment Network Cohort Study; OHTN: Ontario HIV Treatment Network; OR: odds ratio; PHOL: Public Health Ontario Laboratories; REB: Research Ethics Board; SDH: social determinants of health; US: United States